Los Basidiolíquenes de Costa Rica - Gómez P., Luis Diego (Revista de Biología Tropical, 1972)
The Hymenolichens known from Costa Rica are: Herpothallon sanguineum (Herpothallaceae). Cora pavonia and Wainiocora ciferrii (Coraceae), and Dictyonenta sericeum (Dictyonematacea). A key to the families, genera and species is presented, and some ecological notes, mainly to point out the apparent overlapping altitudinal distribution and some preferences as to substratum: that of Herpothalion for the bark of Theobrolla Cacao and of Cora for exposed, lateritic soils or rocky outcrops.